Integrating Unani principles in the understanding and management of non-alcoholic fatty liver disease: a review - Raza, Saquib; Ali, Nazim; Fasihuddeen (International Journal of Research in Medical Sciences, 2026)
Non-Alcoholic Fatty Liver Disease (NAFLD) is a major cause of chronic liver dysfunction globally, affecting nearly 25% of the world’s population. In India, its prevalence ranges from 9% to 32%, with higher occurrence among individuals who are obese or have diabetes mellitus, insulin resistance, hyperlipidaemia, or a sedentary lifestyle. NAFLD encompasses a wide pathological spectrum, beginning with simple hepatic steatosis and potentially progressing to non-alcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma. The disease is strongly associated with mechanisms such as insulin resistance, disturbed lipid metabolism, oxidative stress, inflammation, and hepatic fibrosis. Despite extensive research, modern medicine currently lacks a definitive pharmacological therapy, which has led to growing interest in traditional medical systems, including Unani medicine. According to Unani principles, NAFLD referred to as Ghair Khamri Tashahhum-e-Kabid arises from derangement of the hepatic temperament (Mizaj) and imbalance of humors, particularly an excess of Balgham and Sauda. This imbalance results in obstruction and accumulation of morbid matter within the liver. Common clinical features include fatigue, a feeling of heaviness in the right hypochondrium, impaired digestion, and changes in temperament. Management in Unani medicine aims to restore humoral balance through Ilaj-bil-Ghiza (dietotherapy), Ilaj-bit-Tadbeer (regimental therapy), and Ilaj-bil-Dawa (pharmacotherapy). Several Unani medicinal plants, such as Afsanteen (Artemisia absinthium), Darchini (Cinnamomum zeylanicum), and Mako (Solanum nigrum), possess hepatoprotective, antioxidant, and anti-inflammatory properties that are relevant to the management of NAFLD. Thus, Unani medicine offers a holistic conceptual framework for understanding liver disorders analogous to NAFLD. Integrating classical Unani knowledge with contemporary scientific research on metabolic and herbal mechanisms may provide effective preventive and therapeutic approaches. However, further clinical studies are required to validate the efficacy and safety of Unani interventions in the management of NAFLD.